Mixed Large Cell Neuroendocrine Carcinoma and Adenocarcinoma with Spindle Cell and Clear Cell Features in the Extrahepatic Bile Duct - John Wysocki; Rishi Agarwal; Laura Bratton; Jeremy Nguyen; Mandy Crause Weidenhaft; Nathan Shores; Hillary Z. Kimbrell (Hindawi Limited, 2014)
Mixed adenoneuroendocrine carcinomas, spindle cell carcinomas, and clear cell carcinomas are all rare tumors in the biliary tract. We present the first case, to our knowledge, of an extrahepatic bile duct carcinoma composed of all three types. A 65-year-old man with prior cholecystectomy presented with painless jaundice, vomiting, and weight loss. CA19-9 and alpha-fetoprotein (AFP) were elevated. Cholangioscopy revealed a friable mass extending from the middle of the common bile duct to the common hepatic duct. A bile duct excision was performed. Gross examination revealed a 3.6 cm intraluminal polypoid tumor. Microscopically, the tumor had foci of conventional adenocarcinoma (CK7-positive and CA19-9-postive) surrounded by malignant-appearing spindle cells that were positive for cytokeratins and vimentin. Additionally, there were separate areas of large cell neuroendocrine carcinoma (LCNEC). Foci of clear cell carcinoma merged into both the LCNEC and the adenocarcinoma. Tumor invaded through the bile duct wall with extensive perineural and vascular invasion. Circumferential margins were positive. The patient's poor performance status precluded adjuvant therapy and he died with recurrent and metastatic disease 5 months after surgery. This is consistent with the reported poor survival rates of biliary mixed adenoneuroendocrine carcinomas.